Elderly in Barbados : problems and policies. - Braithwaite, Farley S. (1990)
Provides an overview of the social and economic circumstances affecting Barbados' elderly population. Presents the social policy approaches used to deal with problems of the elderly, together with a tentative assessment of those approaches.